2020
DOI: 10.1590/1808-057x201908100
|View full text |Cite
|
Sign up to set email alerts
|

The influence of recession and macroeconomic variables on sectorial capital structure

Abstract: The aim of this paper is to analyze the influence of the recent recession and of macroeconomic variables over the indebtedness in Brazilian industry sectors. The gap derives from the preference for investigating the reaction of capital structure according to economic sectors. However, it has to be considered that industry sectors react differently to variations in the economic context, since they have different optimal points of capital structure composition. The relevance of the chosen topic lies in carrying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…In the reviewed national literature, as mentioned by Bittencourt and Albuquerque (2018), there is a predominance of approaches that analyze the relationship between a company's indebtedness level and its indirect determinants, from the perspective of various theories of capital structure. In this type of approach, with variations, evidence could be identified that Brazilian companies follow the POT, just as in Bastos and Nakamura (2009), Cardoso andPinheiro (2020), andCorrea et al (2013). Tristão and Sonza (2019), in turn, identified results consistent with the search for an optimal indebtedness level and Nakamura et al (2007) and Oliveira et al (2013) identified mixed results, which did not allow the corroboration of any theory, based on the Brazilian companies under analysis.…”
Section: Literature Reviewmentioning
confidence: 88%
“…In the reviewed national literature, as mentioned by Bittencourt and Albuquerque (2018), there is a predominance of approaches that analyze the relationship between a company's indebtedness level and its indirect determinants, from the perspective of various theories of capital structure. In this type of approach, with variations, evidence could be identified that Brazilian companies follow the POT, just as in Bastos and Nakamura (2009), Cardoso andPinheiro (2020), andCorrea et al (2013). Tristão and Sonza (2019), in turn, identified results consistent with the search for an optimal indebtedness level and Nakamura et al (2007) and Oliveira et al (2013) identified mixed results, which did not allow the corroboration of any theory, based on the Brazilian companies under analysis.…”
Section: Literature Reviewmentioning
confidence: 88%
“…One way to achieve and attain the optimum speed of adjustments is to determine a generalised predictor and aggregated factors that influence it (Gan and Chen, 2021;Giovanni et al, 2021;Cardoso and Pinheiro, 2020;Ezeani, 2019). For example, Haron et al (2013) argued that the speed of adjustment relies on the firm's size and period due to the adjustment costs incurred by the firms.…”
Section: Introductionmentioning
confidence: 99%
“…While Bolarinwe and Adegboye (2020) re-examined the determinants of capital structure in Nigeria using a combination of models like difference generalised method of moments (GMM), system GMM and stochastic frontier analysis (SFA). However, some studies which concentrated on developed countries found contrasting results, while fewer studies were on developing countries (Bajaj et al, 2020;Cardoso and Pinheiro, 2020;Goel, 2019;Ganiyu et al, 2018). The limited study in developing countries like Nigeria may create a misleading assumption that the theory and estimators applied in developed countries can be sustained and generalised in developing countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variável Retorno Ações, calculada com base na variação anual do IBOVESPA serve como uma proxy para as condições gerais do mercado acionário. Pela ótica do market timing (Baker & Wurgler, 2002) sugerido pela teoria e evidências empíricas de que empresas com maiores perspectivas de crescimento tendem a se financiar com ações (Cardoso & Pinheiro, 2020;Frank & Goyal, 2009b;Myers, 1977). Estes resultados estão em linha com os encontrados em outras pesquisas internacionais como (Frank & Goyal, 2009a;Rajan & Zingales, 1995).…”
Section: 𝑅𝑒𝑛𝑡𝑎𝑏𝑖𝑙𝑖𝑑𝑎𝑑𝑒 = 𝐸𝐵𝐼𝑇 𝐴𝑡𝑖𝑣𝑜 𝑇𝑜𝑡𝑎𝑙unclassified